The Role of Guided Bone Regeneration in Enhancing Dental Implant Success - Taghizadeh , Emad; Negargar , Sahar; Nuroozi Larki , Kosar; Saberi Haghighi , Raman; Shahoon , Hossein (Galen Medical Journal, 2024)
Guided Bone Regeneration (GBR) has become an essential technique in dental implantology, particularly for cases with compromised bone volume that impact implant success. This narrative review examines the role of GBR in enhancing dental implant outcomes, focusing on its applications, biological principles, materials, and clinical protocols. GBR utilizes barrier membranes and bone graft materials to foster bone regeneration in deficient areas, creating a stable foundation for implant placement by preventing soft tissue invasion and promoting osteogenic activity. Through a literature review of recent studies, we assess the clinical efficacy of GBR in addressing bone insufficiencies resulting from periodontal disease, trauma, or resorption following tooth loss, with a particular emphasis on how GBR augments implant stability and long-term survival. The review explores various GBR materials, including resorbable and non-resorbable membranes, and graft types such as autografts, allografts, xenografts, and synthetic options. Additionally, advancements in bioactive membranes, growth factor-enhanced materials, and 3D-printed scaffolds are discussed for their potential to improve regenerative outcomes and reduce procedural complications. Best practices in clinical protocols, including preoperative planning, precise membrane placement, and post-operative care, are analyzed to highlight factors that enhance GBR success. Comparative analyses indicate that GBR significantly improves implant survival and reduces marginal bone loss, demonstrating its efficacy in complex cases. Despite its high success rate, GBR has limitations, such as the potential for complications like peri-implantitis and membrane exposure. The paper concludes with suggestions for future research on optimizing GBR materials, enhancing biological responses, and improving long-term outcomes to broaden its application in dental implantology. This review serves as a resource for clinicians and researchers seeking to maximize implant success through advanced GBR techniques.